2017
DOI: 10.1089/lap.2017.0298
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic Versus Open Congenital Diaphragmatic Hernia Repair: Single Tertiary Center Review

Abstract: In our experience, thoracoscopic CDH repair was performed safely and with similar outcomes compared to open repair. In addition to improved cosmesis, thoracoscopic repair may avoid some of the long-term complications of laparotomy. In our series, none of the thoracoscopic CDH repairs recurred. We conclude that thoracoscopic CDH repair is a safe and appropriate technique for select neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 19 publications
0
26
0
6
Order By: Relevance
“…Length of hospital stay was reported in 11 NRSs comparing 3,499 patients. [14][15][16][17][18][19][20][21][22][23][24] Hospital stay was shorter in patients undergoing VATS diaphragmatic hernia repair in five NRSs (45.5%) including 3,287 patients (93.3%). 14,15,[19][20][21] Postoperative ventilation time was compared in 11 NRSs reporting on 562 patients.…”
Section: Advantages Of Vatsmentioning
confidence: 99%
See 1 more Smart Citation
“…Length of hospital stay was reported in 11 NRSs comparing 3,499 patients. [14][15][16][17][18][19][20][21][22][23][24] Hospital stay was shorter in patients undergoing VATS diaphragmatic hernia repair in five NRSs (45.5%) including 3,287 patients (93.3%). 14,15,[19][20][21] Postoperative ventilation time was compared in 11 NRSs reporting on 562 patients.…”
Section: Advantages Of Vatsmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21][22][23][24] Hospital stay was shorter in patients undergoing VATS diaphragmatic hernia repair in five NRSs (45.5%) including 3,287 patients (93.3%). 14,15,[19][20][21] Postoperative ventilation time was compared in 11 NRSs reporting on 562 patients. [14][15][16][17][18][19][20][23][24][25][26] Shorter postoperative ventilation after VATS repair was found in seven studies (63.6%) including 427 patients (45.1%).…”
Section: Advantages Of Vatsmentioning
confidence: 99%
“…It had been debated in earlier studies that recurrences are higher (ranging from 5-40%) following thoracoscopic repair than open repair [5,15,17,18]. In 2017 Tyson., et al [19] in his study reported zero recurrence rate in thoracoscopic cohort and Liem., et al reported 3.6% recurrence rate [7]. In our study we observed only 2.7% recurrence rate.…”
Section: Reason Is To Perform Intracorporeal Suturing Easily In Everymentioning
confidence: 88%
“…Не подлежит сомнению, что торакоскопия избавляет пациентов от образования вентральных грыж и внутрибрюшных адгезий. A. Tyson [10] и соавт. сообщают о 4 больных с послеоперационными грыжами брюшной стенки и 5 больных, у которых после открытых операций развился спаечный илеус.…”
Section: Discussionunclassified
“…До сих пор не ясно, может ли эта технология использоваться с оптимальными результатами в госпиталях, в которых проходят лечение незначительное количество пациентов. В настоящее время имеется несколько отчетов о лечении детей с ВДГ с использованием минимально инвазивных технологий [2][3][4][5][6][7][8][9][10]. Известно несколько РКИ, в которых в основном обсуждались вопросы изучения изменения уровня острофазовых пептидов [11] и газового состава крови [12] в ходе реконструкции диафрагмальных дефектов.…”
Section: Original Articlesunclassified